2015
DOI: 10.1016/j.nbd.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of APP gamma-secretase restores Sonic Hedgehog signaling and neurogenesis in the Ts65Dn mouse model of Down syndrome

Abstract: Neurogenesis impairment starting from early developmental stages is a key determinant of intellectual disability in Down syndrome (DS). Previous evidence provided a causal relationship between neurogenesis impairment and malfunctioning of the mitogenic Sonic Hedgehog (Shh) pathway. In particular, excessive levels of AICD (amyloid precursor protein intracellular domain), a cleavage product of the trisomic gene APP (amyloid precursor protein) up-regulate transcription of Ptch1 (Patched1), the Shh receptor that k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
0
39
1
Order By: Relevance
“…In contrast, immediately after the end of treatment Ts65Dn mice had a significantly larger number of both SYN and PSD-95 immunoreactive puncta (Giacomini et al, 2015). These results show that the restoration of connectivity observed in the DG of P15 mice at the end of treatment does not outlive treatment cessation and suggests that continuous treatment may be necessary in order to maintain this effect.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, immediately after the end of treatment Ts65Dn mice had a significantly larger number of both SYN and PSD-95 immunoreactive puncta (Giacomini et al, 2015). These results show that the restoration of connectivity observed in the DG of P15 mice at the end of treatment does not outlive treatment cessation and suggests that continuous treatment may be necessary in order to maintain this effect.…”
Section: Discussionmentioning
confidence: 97%
“…Treatment of newborn Ts65Dn mice, a mouse model of DS, with the Shh pathway agonist SAG ameliorates cerebellar development defects, effectively restoring the granule cell precursor pool [49]. Hippocampal neurogenesis is impaired in Ts65Dn mice, a model of Down syndrome, and neurogenesis is normalized when the mice are treated with a γ-secretase inhibitor [51]. Shh signaling is required for restoration of neurogenesis because inhibition of γ-secretase does not restore neurogenesis when mice are treated with cyclopamine.…”
Section: Shh Signaling and Neurological Disordersmentioning
confidence: 99%
“…43 In support of this observation, a recent study has been demonstrated that g-secretase inhibitor treatment normalized AICD levels and restored impaired neurogenesis and Sonic Hedgehog signaling in Ts65Dn-derived neurospheres. 50 The crucial role of AICD is underscored by an agedependent decrease in BrdU incorporation and DCX-immunoreactive cells in the dentate gyrus of AICD transgenic mice. While neuronal differentiation was unaffected, proliferation and survival of progenitor cells was strongly reduced.…”
Section: Role Of the Aicd Fragment In Altered Neurogenesismentioning
confidence: 99%